2010
DOI: 10.1021/jp911857m
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Laser-Ablated Zirconium Atoms within a Supersonic Expansion: Insertion versus Radical Mechanism

Abstract: In a laser ablation type microreactor followed by supersonic expansion, zirconium atoms have been reacted with methyl fluoride, CH(3)F (MeF), and mixtures of MeF and dimethylether, CH(3)-O-CH(3) (DME) seeded in He. With both mixtures, only a number of simple fluorinated products are formed, and they have been identified by one-photon ionization. All products can be linked to radical reactions either with F atoms, CH(3), or ZrF(1, 2, 3) radicals. No insertion products of the Grignard reagent type, F -Zr-CH(3) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
0
16
1
Order By: Relevance
“…In accordance with the data provided in Table 3, the calculated energy for the 1 A 0 electronic state was only slightly less than the energy values corresponding to the triplet states, whereas the energy for singlet state 1 A 00 was approximately 26 kcal/mol greater than that of the most stable singlet state. Interestingly, these energy values differed markedly from those reported by Soorkia et al [16] For example, the energy difference reported by these authors for the 1 A 0 and 3 A 0 electronic states was 72 kcal/ mol.…”
Section: Methodscontrasting
confidence: 78%
See 3 more Smart Citations
“…In accordance with the data provided in Table 3, the calculated energy for the 1 A 0 electronic state was only slightly less than the energy values corresponding to the triplet states, whereas the energy for singlet state 1 A 00 was approximately 26 kcal/mol greater than that of the most stable singlet state. Interestingly, these energy values differed markedly from those reported by Soorkia et al [16] For example, the energy difference reported by these authors for the 1 A 0 and 3 A 0 electronic states was 72 kcal/ mol.…”
Section: Methodscontrasting
confidence: 78%
“…The channels leading to the radical products can be useful for rationalizing the experimental data for the reaction of ablated zirconium atoms with CH 3 F within a supersonic expansion because the ZrF· and ·CH 3 species can be linked to the products detected by the gas‐phase determinations . However, they do not provide a plausible description of the process leading from the reactants to the H 3 CZrF and H 2 CZrHF complexes detected under the matrix conditions (as well as theoretically).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another surprising fact is that the products observed for reactions occurring under matrix‐isolation conditions often differ from those determined in less constrained media. For example, the products detected for the reaction of fluoromethane with zirconium atoms within a supersonic expansion can be linked to the radical species F, CH 3 and Zr−F, whereas the products observed for the same reaction under matrix confinement are the inserted structures H 3 C−Zr‐F and H 2 C=ZrHF . Likewise, the products obtained by dropping Fe atoms into CCl 4 deposited on a cold FeO(111) surface, C 2 Cl 4 , C 2 Cl 6 , OCCl 2 , CO, FeCl 2 and FeCl 3 , support a radical mechanism, whereas the same reaction under matrix conditions yields high‐oxidation state complexes containing Fe−C bonds.…”
Section: Introductionmentioning
confidence: 99%